Strategi Pengelolaan Berkelanjutan Pesisir dan Laut Pulau Nusa Manu dan Pulau Nusa Leun di Kabupaten Maluku Tengah - Ilham Marasabessy; Achmad Fahrudin; Zulhamsyah Imran; Syamsul B. Agus (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Coastal and small islands are faced with various significant challenges. The trend shows that the region suffered largely from habitat destruction, changes on natural processes of ecosystems andpollution. Coastal and small islands regions became increasingly complex as conflicts of interest occur, both within the community and at the government level. Thus, activities to be placed within this region should consider the compatibility between needs and the region’s ability in providing resources. This study aims to develop a management strategy for unpopulated islands in utilization of natural resources. The research was conducted through descriptive evaluative method, using spatial analysis to obtain suitability between the waters and the carrying capacity of the area usingArcGIS 10.3. On the other hand, management strategies were formulated using Analytic Hierarchy Process (AHP) model. The ecological potentials of Nusa Manu and Nusa Leun Islands covers diving, snorkeling tours, mangrove tracking and beach tourism, grouper fish aquaculture within floating netcages and fishing grounds. The potentials are suitable and can be utilized for various activities with priority on conservation-based marine ecotourism. This management strategy sides with the people, opens employment opportunities and able to encourage economic growth while maintaining the sustainability aspects of natural resources.